2020
DOI: 10.21203/rs.3.rs-45699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personal Health Perceptions as Predictors to Medication Adherence in a Prospective Cohort Study Among Patients with Multiple Sclerosis

Abstract: Background: Though adherence to disease-modifying therapies (DMTs) among persons with multiple sclerosis (PwMS) varies and is often below 80%, only few prospective studies on adherence examined predictors beyond demographic and clinical characteristics. Objectives: Identify antecedents to adherence and persistence in a prospective design among PwMS.Methods: PwMS (n=186) were prospectively assessed at three time points: baseline, 6 and 12 months later. Clinical, demographic information and patient-reported medi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…An effective application of the HBM model has been conducted to predict IM nonadherence among RTPs in our transplant center, and our results indicated that perceived seriousness and perceived barriers were closely associated with IM nonadherence (Xia et al, 2019). Also, a recent study indicated that beliefs about medications were more powerful predictors to nonadherence than clinical or sociodemographic factors among patients with multiple sclerosis (Neter et al, 2021). The theory of planned behavior (TPB), as a cognitive model, also exhibited several advantages to predict a wide range of health-related behaviors (Andrew et al, 2016;Caru et al, 2020).…”
Section: Introductionmentioning
confidence: 54%
“…An effective application of the HBM model has been conducted to predict IM nonadherence among RTPs in our transplant center, and our results indicated that perceived seriousness and perceived barriers were closely associated with IM nonadherence (Xia et al, 2019). Also, a recent study indicated that beliefs about medications were more powerful predictors to nonadherence than clinical or sociodemographic factors among patients with multiple sclerosis (Neter et al, 2021). The theory of planned behavior (TPB), as a cognitive model, also exhibited several advantages to predict a wide range of health-related behaviors (Andrew et al, 2016;Caru et al, 2020).…”
Section: Introductionmentioning
confidence: 54%